Pengaruh Perbedaan Waktu Penangkapan Pagi dan Malam Hari Pada Hasil Tangkapan Ikan Menggunakan Alat Tangkap Mini Purse Seine - Nainggolan Surya Alma; Yusrudin Yusrudin; Sumaryam Sumaryam (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
Purse seine fishing gear is a type of fishing equipment consisting primarily of a large net, designed to catch both large and small pelagic fish. This study aimed to (1) determine the effect of time differences—morning and evening—on the catch of flying fish using mini purse seine fishing gear, and (2) identify the composition and dominant species caught in each fishing period. The research was conducted at Banda Neira Pier, Banda District, Central Maluku Regency, Maluku, Indonesia. An experimental fishing method was applied, and data were analyzed using the Two Sample t-Test. Fishing operations were carried out over 16 trips, equally distributed between morning and evening sessions. The total recorded catch comprised 15,078 kg of mackerel (Rastrelliger sp.), 4,017 kg of skipjack (Katsuwonus pelamis), 18,743 kg of deho (Euthynnus affinis), and 45,601 kg of flying fish (Decapterus sp.). In the morning, the total catch reached 36,005 kg, dominated by flying fish, whereas in the evening, it was 50,250 kg, also dominated by flying fish. Statistical analysis using the Two Sample t-Test focused on the dominant species, flying fish, and revealed a p-value of <0.05. This indicates a significant difference in the composition of the catch between morning and evening fishing activities. The findings suggest that fishing time plays a crucial role in catch volume, particularly for flying fish, with evening fishing showing higher yields. These results can be valuable for optimizing fishing strategies, improving efficiency, and supporting sustainable fisheries management in Banda Neira and similar pelagic fishing grounds.